Anxiety, depression, female sexual dysfunction in women seeking infertility treatment in two Malaysian hospitals - Ahmad, Zuraida (2010)
Background: Infertility is defined as inability to conceive after 1 year of unprotected sex. It is associated with substantial level of stress. Previous literature has reported that infertility women reported higher level of depressive and anxiety symptoms than women in the fertile population. Another consequence that has been reported in the infertility women is increased level of sexual dysfunction. Studies have reported infertility women at an increased risk of developing sexual dysfunction compared to controls. Objectives: The aim of the study was to determine the prevalence of anxiety, depression and sexual dysfunction in women seeking infertility treatment. This study also aimed to determine the association between anxiety, depression and reproductive characteristics in women seeking infertility treatment and to determine the correlation between sexual dysfunction and anxiety and depression in women seeking infertility treatment. In addition, this study also compares the level of anxiety, depression and sexual dysfunction between different groups of sociodemographic factors in infertile female patient. Method: This was a cross sectional study. The subjects consisted of 159 women seeking infertility treatment in infertility clinics in Hospital Universiti Sains Malaysia and Hospital Raja Perempuan Zainab II. They were selected through non probable sampling method. Anxiety and depression was assessed with the Malay version of Hospital Anxiety and Depression Scale (HADS) and sexual dysfunction was assessed by the Malay Version of Female Sexual Function Index (MVFSFI). Patients that scored above the cut off points for depression and anxiety in HADS questionnaire will be interviewed using Mini International Neuropsychiatric Interview (MINI) to make a diagnosis of Anxiety and/or Depression according to DSM-IV. The outcome measures were the percentages of patient who had anxiety, depression and female sexual dysfunction, the association between anxiety, depression with type of infertility, cause of infertility and duration of infertility. The correlation between anxiety, depression with female sexual dysfunction was determined. Descriptive analysis, Fisher's Exact test, Cramer's V test, Pearson's Correlation test and Mann-Whitney U test were appropriately used in data analysis. Results: By HADS questionnaire 4.4% was found to have anxiety, 0.6% (1 subject) had depression None of the participants who had reached the cut off point for anxiety and depression of HADS and who were then interviewed using MINI was diagnosed to have any anxiety or depressive disorder according to DSM IV criteria .. Only 3.1% had sexual dysfunction detected by MVFSFI. There were no association found between anxiety and depression with type of infertility, cause of infertility and duration of infertility. However there were significant correlations between anxiety and depression with female sexual dysfunction. There is no significant difference in anxiety level between different groups of socidemographic factors. There are significant difference in depression between different groups of race, education level and income. There is significant difference in sexual dysfunction in different duration of marriage. Conclusion: The level of anxiety, depression and female sexual dysfunction were low in women seeking infertility treatment. It appeared that the level of anxiety and depression have not led to clinical impairment. However there were significant correlations between anxiety and depression with female sexual dysfunction. There is no significant difference in anxiety level between different groups of socidemographic factors. There are significant difference in depression between different groups of race, education level and income. There is significant difference in sexual dysfunction in different duration of marriage.